Model predictive control for a dual active bridge inverter with a floating bridge - Chowdhury, Shajjad; Wheeler, Patrick; Gerada, C.; Patel, Chintan (Institute of Electrical and Electronics Engineers, 2016)
This paper presents a Model Predictive Control technique applied to a dual active bridge inverter where one of the bridges is floating. The proposed floating bridge topology eliminates the need for isolation transformer in a dual inverter system and therefore reduces the size, weight and losses in the system. To achieve multilevel output voltage waveforms the floating inverter DC link capacitor is charged to the half of the main DC link voltage. A finite-set Model Predictive Control technique is used to control the load current of the converter as well as the floating capacitor voltage. Model predictive control does not require any switching sequence design or complex switching time calculations as used for SVM, thus the technique has some advantages in this application. A detailed analysis of the converter as well as the predictive control strategy is given in this paper. Simulation and experimental results to validate the approach are also presented.